2016
DOI: 10.1038/ncomms10307
|View full text |Cite
|
Sign up to set email alerts
|

DCAF1 controls T-cell function via p53-dependent and -independent mechanisms

Abstract: On activation, naive T cells grow in size and enter cell cycle to mount immune response. How the fundamental processes of T-cell growth and cell cycle entry are regulated is poorly understood. Here we report that DCAF1 (Ddb1–cullin4-associated-factor 1) is essential for these processes. The deletion of DCAF1 in T cells impairs their peripheral homeostasis. DCAF1 is upregulated on T-cell receptor activation and critical for activation-induced T-cell growth, cell cycle entry and proliferation. In addition, DCAF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…However, regulation of p53 ubiquitylation remains incompletely understood and may involve other E3 ligases (Brooks and Gu, 2006). In keeping with this, Guo et al (2016) found that MDM2 overexpression increased p53 polyubiquitylation in U2OS cells, and that this effect was reversed by concomitant loss of DCAF1. However, the exact mechanism by which DCAF1 promotes ubiquitylation and degradation of p53 via MDM2 remains to be determined.…”
Section: Function Of Dcaf1 In Normal Physiology and Cancersupporting
confidence: 66%
See 3 more Smart Citations
“…However, regulation of p53 ubiquitylation remains incompletely understood and may involve other E3 ligases (Brooks and Gu, 2006). In keeping with this, Guo et al (2016) found that MDM2 overexpression increased p53 polyubiquitylation in U2OS cells, and that this effect was reversed by concomitant loss of DCAF1. However, the exact mechanism by which DCAF1 promotes ubiquitylation and degradation of p53 via MDM2 remains to be determined.…”
Section: Function Of Dcaf1 In Normal Physiology and Cancersupporting
confidence: 66%
“…This study showed that DCAF1 depletion in U2OS cells increases expression of p53 and several of its target genes, including those encoding the cyclin-dependent kinase inhibitors p21 and p27. Consistent with this finding, conditional inactivation of Dcaf1 in T lymphocytes was found to stabilize p53 levels in DCAF1-deficient T cells and increase levels of p21 and the pro-apoptotic protein Bax (both products of p53 target genes) (Guo et al, 2016). p53 is known to be polyubiquitylated and degraded by the E3 ligase MDM2 (Haupt et al, 1997; Kubbutat et al, 1997).…”
Section: Function Of Dcaf1 In Normal Physiology and Cancermentioning
confidence: 58%
See 2 more Smart Citations
“…This is despite knockdown of DCAF1 in these cells, which reduces the DCAF1 protein abundance by approximately 50% (Figure S2B). In addition, at least 13 proteins co-immunoprecipitating with Vpr here have been reported previously to physically interact with DCAF1 alone (Coyaud et al., 2018, Guo et al., 2016, Hossain et al., 2017), of which 11 are not regulated by Vpr, and two, CEP78 and IQGAP2, are upregulated by Vpr, explaining their presence in this list of proteins.…”
Section: Resultsmentioning
confidence: 67%